Evolution of rust layers on carbon steel and weathering steel in high humidity and heat marine atmospheric corrosion. (15th February 2020) - Fan, Yueming; Liu, Wei; Li, Shimin; Chowwanonthapunya, Thee; Wongpat, Banthukul; Zhao, Yonggang; Dong, Baojun; Zhang, Tianyi; Li, Xiaogang
Abstract: The evolution of the rust layers on carbon steel and weathering steel in high humidity and heat marine atmospheric environment was investigated by wet/dry cyclic acceleration corrosion tests in this study. The corrosion process of carbon steel and weathering steel was divided into two stages and the reasons for the changes in the corrosion rates of two steels were different. The composition phase of the inner rust layer of weathering steel was mainly goethite, whereas that of carbon steel was mainly akaganeite. Rust resistance ( R r ) performed better than charge transfer resistance ( R t ) in evaluating the protection performance of rust layer. As the corrosion proceeded, the evolution of the cathodic process of weathering steel was not obvious, whereas that of carbon steel was irregular.